Newly identified species from the dog dental plaque microbiome highlight little overlap with humans - Vitor Heidrich; Gloria Fackelmann; Milka Malesevic; Federica Armanini; Hrituraj Dey; Claudia Mengoni; Nemanja Stanisavljevic; Goran Vukotic; Nicola Segata (npj Biofilms and Microbiomes)
Abstract Understudied pet-associated microbiomes represent a rich source for the discovery of microbial taxa important for pet and human health. From a cohort of 23 dogs, we sampled and metagenomically sequenced 64 dental plaque microbiomes, generating 1945 metagenome-assembled genomes spanning 347 microbial species, including 277 undercharacterized species without cultivated representatives. Integration with human microbiome data revealed the dog plaque microbiome is more diverse than – and shows little overlap (5.9% species in common) with – the human plaque microbiome, even though some shared periodontal pathobionts arise as a potential concern.